Oncology at a glance - Dark, Graham; Hennah, Lindsay (At a glance series (Oxford, England), 2025)
"This title in the market-leading at a Glance series brings together fundamental information on cancer biology and treatment to provide a holistic understanding of oncology. It explores both relevant scientific content and key human issues, including communication and palliative care"-- Provided by publisher.